EKSTRAKSI ZAT WARNA ALAM DARI BONGGOL TANAMAN PISANG (Musa paradiasciaca L.) DENGAN METODE MASERASI, REFLUKS, DAN SOKLETASI - Anak Agung Bawa Putra; Ni Wayan Bogoriani; Ni Putu Diantariani; Ni Luh Utari Sumadewi (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
We have conducted research on natural dyes extraction of banana (Musa paradiasiaca L.) weevil. The rendement concentration, its color, and their functional groups were determined using phytochemical test and ultraviolet-visible spectrophotometer. Extraction of natural dyes in the study was conducted by three methods namely maceration, reflux, and soxletation by using four kinds of extracting solvent including water, ethanol, acetone, and n-hexane. Color extract in water was dark brown, in ethanol and acetone was light brown, and in n-hexane was yellow. Each extract obtained by the three methods of each solvent was concentrated, their rendement were determined. The yields obtained by the maceration method using water was 8.12%, ethanol 2.40%, acetone 0.52%, and n-hexane 1.16%. The yields of the reflux method were 8.68%, 1.84%, 1.44%, and 1.04% respectively. The yields of the soxletation method were 4.80%, 1.12%, 0.44%, 0.56% respectively. The phytochemical test showed that the banana weevil dyes contained tannins and flavonoids. Absorption of the wavelength of energy ultra violet – visible detected at a wavelength between 200 nm up to 400 nm.